2017
DOI: 10.1016/j.rmed.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

The performance of the GAP model in patients with rheumatoid arthritis associated interstitial lung disease

Abstract: Background Rheumatoid arthritis-associated interstitial lung disease (RA-ILD) is associated with significant morbidity and mortality. Similarities have been observed between patients with idiopathic pulmonary fibrosis (IPF) and the UIP (usual interstitial pneumonia) form of RA-ILD. The GAP (gender, age, physiology) model has been shown to predict mortality in patients with IPF, but its ability to predict mortality in RA-ILD is not known. Methods We identified 309 patients with RA-ILD at 4 academic centers wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 29 publications
1
36
1
2
Order By: Relevance
“…More recent studies tend to show longer survival which may be attributed to improved radiological techniques and increased awareness of RA-ILD leading to earlier diagnosis (Table 4). Previous studies have reported UIP as the predominant radiological pattern and predictor of mortality [14,42]; however, recent studies report a UIP proportion of 40%-54% [40,47]. A recent study showed that radiology-based prediction models in RA-ILD can identify patients with a progressive fibrosis phenotype [112], and that the visual extent of ILD in combination with FVC values, as previously seen in scleroderma [113], predicts outcome in RA-ILD.…”
Section: Prognosismentioning
confidence: 97%
See 2 more Smart Citations
“…More recent studies tend to show longer survival which may be attributed to improved radiological techniques and increased awareness of RA-ILD leading to earlier diagnosis (Table 4). Previous studies have reported UIP as the predominant radiological pattern and predictor of mortality [14,42]; however, recent studies report a UIP proportion of 40%-54% [40,47]. A recent study showed that radiology-based prediction models in RA-ILD can identify patients with a progressive fibrosis phenotype [112], and that the visual extent of ILD in combination with FVC values, as previously seen in scleroderma [113], predicts outcome in RA-ILD.…”
Section: Prognosismentioning
confidence: 97%
“…Radiological findings in RA-ILD include ground glass-opacities, reticulation, consolidation, honeycombing, and nodules similar to other ILD subtypes [30,33,38,39]. The most common HRCT patterns in RA-ILD are UIP and NSIP, while organizing pneumonia (OP) and bronchiolitis are less common ( Figure 1) (Table 1) [8,14,[38][39][40][41][42][43][44][45][46][47]. Studies show a fairly good correlation between HRCT and histopathological findings with the least concordance in the diagnosis of UIP and NSIP [39,42,46].…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a radiological and/or histological pattern of usual intersitial pneumonia (UIP) has been associated with increased mortality with poor prognosis also seen in patients with specific radiological features of UIP such as honeycombing and traction bronchiectasis [26][27][28]. The prognostic significance of a UIP pattern is seen across ILD subtypes, indicating that morphological pattern may be more prognostically important compared to the specific etiology of the disease [9,29,30]. An acute exacerbation is the most extreme type of ILD progression, characterized by a sudden and usually severe respiratory deterioration with new bilateral opacities on high-resolution computed tomography (HRCT) [31].…”
Section: Risk Factors For Progressionmentioning
confidence: 99%
“…Morisset et al . 46 developed a mortality model for patients with rheumatoid arthritis-associated interstitial lung disease. The cross-validated C-index of the final model (a multivariate CPH model) was 0.75, similar to our results.…”
Section: Discussionmentioning
confidence: 99%